Establishment and Validation of a Ferroptosis-Related Long Non-Coding RNA Signature for Predicting the Prognosis of Stomach Adenocarcinoma - Zhang, Shuqiong; Zheng, Naisheng; Chen, Xiaocui; Du, Kun; Yang, Junyao; Shen, Lisong (Frontiers in Genetics, 2022)
Background: Ferroptosis is a form of regulated cell death that follows cell membrane damage and mostly depends on iron-mediated oxidative. Long non-coding RNAs (LncRNAs) are associated with the development of a variety of tumors. Till date, LncRNAs have been reported to intervene in ferroptosis. Therefore, we intended to provide a prognostic ferroptosis-related-lncRNA signature in stomach adenocarcinoma (STAD). Methods: We downloaded ferroptosis-related genes from the FerrDb database and RNA sequencing data and clinicopathological characteristics from The Cancer Genome Atlas. Gene differential expression analysis was performed using the “limma” package. We used Cox regression analysis to determine the ferroptosis-related lncRNAs signature with the lowest AIC value. The Kaplan–Meier curve, ROC curve, and nomogram were used to evaluate the prognostic value of the risk score. Gene set enrichment analysis (GSEA) was used to explore the biologic functions of the three ferroptosis-related lncRNAs. LINC01615 expression in gastric cancer cell lines and tissues was measured by real-time PCR. A nuclear-cytoplasmic fractionation assay was used to analyze the subcellular localization for LINC01615. Furthermore, we used bioinformatics to predict potential target microRNAs (miRNAs) of LINC01615 and their target ferroptosis-related mRNAs. Results: Three ferroptosis-related-lncRNA signatures (AP000695.2, AL365181.3, and LINC01615) were identified, and then Kaplan–Meier, Cox regression analyses, and ROC curve confirmed that the ferroptosis-related-lncRNA model could predict the prognosis of STAD. The GSEA indicated that the three ferroptosis-related lncRNAs might be related to the extracellular matrix and cellular activities. LINC01615 is highly expressed in gastric cancer cell lines and tissues. A nuclear-cytoplasmic fractionation assay confirmed that in gastric cancer cell lines, most LINC01615 was enriched in the cytoplasm. Bioinformatics further predicts four potential target miRNAs of LINC01615 and then figured out 26 target ferroptosis-related mRNAs. Conclusion: We established a three-ferroptosis-related-lncRNA model (AP000695.2, AL365181.3, and LINC01615) that can predict the prognosis of STAD patients. We also expected to provide a promising target for LINC01615 for research in the future, which was highly expressed in gastric cancer and cell lines and acted as a ceRNA to get involved in ferroptosis.